Novel Frog Skin-Derived Peptide Dermaseptin-PP for Lung Cancer Treatment: In vitro/vivo Evaluation and Anti-tumor Mechanisms Study - Dong, Ziyi; Hu, Haiyan; Yu, Xianglong; Tan, Li; Ma, Chengbang; Xi, Xinping; Li, Lei; Wang, Lei; Zhou, Mei; Chen, Tianbao; Du, Shouying; Lu, Yang (Frontiers in Chemistry, 2020)
Lung cancer is the major cause of cancer deaths worldwide, which has the highest incidence and mortality among men and women in China. The first-line therapy for lung cancer treatment is the platinum-based chemotherapy drugs such as cisplatin. However, the application of present chemotherapies is limited by severe side effects, which stimulates the discovery of new drugs with new anti-tumor mechanisms and fewer side effects. Beneficially, many antimicrobial peptides (AMPs) from frog skin were reported to exhibit potent anti-cancer activities low toxicity, high selectivity and a low propensity to induce resistance. In this study, we first reported an AMP named Dermaseptin-PP, from a rarely studied frog species, Phyllomedusa palliata. Dermaseptin-PP exhibited selective cytotoxicity on H157, MCF-7, PC-3 and U251 MG cancer cells instead of normal HMEC-1 cells with low hemolytic effect. Furthermore, on H157 subcutaneous tumor model of nude mice, Dermaseptin-PP was found to perform potent in vivo anti-tumor activity in a dose-related manner without obvious hepatopulmonary side effects. Further mechanisms investigation by laser confocal observation, flow cytometry assay and immunohistochemical analysis unraveled that Dermaseptin-PP could disrupt H157 cell membranes, and induce H157 cell apoptosis via both endogenous mitochondrial and exogenous death receptor apoptosis pathways. Herein, we emphasize that the membrane disrupting and the apoptosis activation effects of Dermaseptin-PP both depend on its concentration. Overall, a novel frog skin-derived AMP, Dermaseptin-PP with strong antimicrobial and effective anti-tumor activity by distinct mechanisms has been identified for the first time. Moreover, this study revealed the possibility of Dermaseptin-PP for lung cancer treatment and provided a new perspective for designing novel AMP-based anti-tumor candidates with low risk of cytotoxicity.